PRODUCTION OF ESSENTIAL OILS AS YOUTH EMPOWERMENT MODEL ORPHANAGE AND ISLAMIC BOARDING SCHOOL - warsito warsito warsito; suratmo suratmo; sukardi sukardi (Journal of Innovation and Applied Technology, 2017)
Essential oils for the people of Indonesia can be used as an alternative source of income, due to essential oil prices is promising. Life skill training for foster care in Orphanages and boarding schools through the entrepreneurial coaching essential oil production is believed to be able to provide foster care in order to have adequate life skill, so post away from orphanages or boarding schools can do independent business. Architecture tools distilled water-steam system using stainlesteel. The results of the activities showed that the youth partners able to do practice cultivation of citronella fragrance begins with how to cultivate the land, planting and maintaining plant citronella scented with trial cultivation of land covering an area of 600 m2 total number of seeds and citronella scented 4,000 rods. Essential oil production practices began with the practice of how to harvest, how to enter material into the appliance distilled with a capacity of 25-30 kg, the process of distillation and separation of essential oil from destilat. The results of the practice of cultivation of citronella scented Lemongrass scented plants produce 1 clump average contains 170 stem (3.25 – 3.75 kg) and total production reached 1.8 tons of leaves of the Lemongrass scented with essential oils as much as product quantities 14.40 kg.